KONSEP KEBAHAGIAAN MENURUT IBNU SINA SOLUSI MENGATASI KRISIS EMOSIONAL BAGI GEN. - Ahmad Fernanda; Annisa Suryani Oktapia; Muhammad Rezky Fauzi (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This research aims to examine in depth Ibn Sina's thoughts on the concept of happiness and implement it in the life of Gen. Z in the modern era. The research method used is qualitative research with an exploratory analysis approach. The data sources used are secondary data sources from Kitab an-Najah and Kitab ash-Syifa by Ibn Sina as well as books and articles based on OJS (Opern Journal System) about the concept of happiness through Sufism. Data processing techniques are carried out by processing library materials (library research). Techniques in analyzing data analyzed by exploratory descriptive analysis using reduction, display, and verification techniques. The results of the research: First, the concept of happiness according to Ibn Sina is the balance between soul and mind by keeping lust and anger. Second, some steps that can be taken by Gen.Z to apply the values of happiness from Ibn Sina, such as: Developing the potential of reason and knowledge deeply and continuously; Controlling lust and emotions that can disturb the balance of the soul; Paying attention to physical health and building a social environment that supports the growth of a healthy soul; Honing and strengthening the spiritual and moral dimensions. Gen. Z can build mental resilience and find the authentic meaning of happiness.